ONLINE BUSINESS PRACTICES FOR VIDEO-BASED LEARNING IN DISCOVERY ENGLISH ACADEMY - Yudha, Indra Pradipa (jfpublisher, 2022)
This business plan aims to analyze the business performance of online video-based learning of Discovery English Academy, to find out the comparison of business performance with the business plan of online video-based learning of Discovery English Academy, and to know the implementation of marketing strategies and production aspects in online video- based learning Discovery English Academy. In the implementing process of the online video-based learning Discovery English Academy6, it was found that there were two main problems when launching the online video-based learning product of Discovery English Academy, including; promotion issues, and also selling price issues. In implementing this business practice, Discovery English Academy uses the Digital Channel Revolution marketing strategy, Integrated Marketing Communication (IMC), Brand Awareness, as well as Pull and Push Marketing Strategy to overcome promotional problems. In addition to the problem of selling prices, Discovery English Academy uses a Discount Strategy using a promo code. From the implementation of its business practice, it can be concluded that the optimization of multiple social media channels and also the initial cost determination are the two most essential aspects in carrying out the Discovery English Academy's online video- based learning business practice.